2016
DOI: 10.1108/ijcthr-08-2015-0095
|View full text |Cite
|
Sign up to set email alerts
|

Does managerial efficiency relate to customer satisfaction? The case of Parisian boutique hotels

Abstract: Purpose The purpose of this study is to examine the relationship between the managerial efficiency and the customer satisfaction of Parisian boutique hotels by using the multi-criteria decision analysis (MCDA) methods. Design/methodology/approach In the first stage, hotels’ managerial efficiency is assessed by data envelopment analysis to establish which hotel has the most efficient performance. In the second stage, the customer satisfaction of these hotels is estimated by the ELECTRE (ELimination et Choix T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 75 publications
(72 reference statements)
0
22
0
Order By: Relevance
“…Due to poor technical efficiency and scale efficiency, the results show that overall efficiency for hotel value is only 42%. The CCR of DEA and the BCC models analyzed the operating efficiency of 25 hotels in 2000 and found that four of them were efficient [33]. In short, DEA is a tool for efficiency evaluation.…”
Section: Data Envelopment Analysis (Dea)mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to poor technical efficiency and scale efficiency, the results show that overall efficiency for hotel value is only 42%. The CCR of DEA and the BCC models analyzed the operating efficiency of 25 hotels in 2000 and found that four of them were efficient [33]. In short, DEA is a tool for efficiency evaluation.…”
Section: Data Envelopment Analysis (Dea)mentioning
confidence: 99%
“…Furthermore, the DEA is a multi-factor productivity model for the purpose of evaluating the relative efficiencies of a homogenous set of decision making units (DMUs) [19] and handles multiple inputs and outputs of the performance evaluation method [20], in line with an ideal quantitative assessment of the performance model [21]. In recent years, DEA has been widely used in tourism research [22][23][24][25][26][27][28][29][30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…Because satisfaction is related to loyalty, it can reduce transaction costs and price elasticity in the future bookings. Zaman et al (2016) discovered that satisfaction was inversely proportional to the efficiency of hotels.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Small city boutique hotels (SCBHs) have incorporated unique characteristics of the local culture (Lee, 2011; Zaman et al , 2016), contributing to create competitive advantage for the destination. There is growing evidence that guests are tired of the standard “cookie-cutter” hotel room (Phillips, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that guests are tired of the standard “cookie-cutter” hotel room (Phillips, 2004). Hotels should integrate functional and aesthetic elements such as style, layout and architecture (Heide et al , 2007; Cheng et al , 2016) and understand that tourist expectations of a destination must be satisfied and even exceeded by the hotel design (Phillips, 2004; Loureiro and Kastenholz, 2011; Zaman et al , 2016). As Lee (2011, p. 709) claims, “just as hotels are interested in increasing their market share, so are destinations.” Differentiation through design based on the hotel’s location history and architecture will strengthen the branding of the destination (Lee, 2011).…”
Section: Introductionmentioning
confidence: 99%